PENGARUH PELATIHAN DAN PEMBERDAYAAN TERHADAP KOMPETENSI DAN KINERJA GURU DI UPTD-PK DEWANTARA - Suraida Fitri; A Hadi Arifin; Yanita Yanita (J-MIND (Jurnal Manajemen Indonesia), 2020)
This study aims to examine the effect of training and empowerment of the competence and performance of teachers in UPTD-PK Dewantara. The data used in this research are as many as 152 teachers in SMA Negeri 1 Dewantara, SMA Negeri 2 Dewantara and SMK Negeri 1 Dewantara. The analysis tool used is Structural Equation Modeling (SEM) using AMOS-20 (Analysis of Moment Structure). The results showed that training and empowerment have a significant influence on competence. Training, empowerment and competence have a significant effect on performance. Competence mediates in full mediation the effect of training on performance. Competence mediates partially mediation in the effect of empowering performance. Keywords: Training, Empowerment, Competence, Performance.